The Effect Of Sales Growth On Stock Prices Through Net Working Capital (Case Study Of Pharmaceutical Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2019 - 2023): - Putri, Marsha Vanessa; Yusnita, Rita Tri; Rahwana, Kusuma Agdhi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the effect of sales growth on share prices through net working capital in pharmaceutical subsector companies listed on the IDX for the 2019 - 2023 period. The method used is a quantitative approach with a research sample of 8 pharmaceutical companies. The data used is secondary data. The analytical tool used in this research is path analysis using Eviews version 12. Based on the research results, it is known that Sales Growth has a significant direct effect on Stock Prices. Sales Growth has a significant effect on Net Working Capital. Net Working Capital has a significant effect on share prices. Sales Growth has a significant effect on Share Prices through Net Working Capital.